Maxillomandibular advancement as the initial treatment of obstructive sleep apnoea: Is the mandibular occlusal plane the key?. Issue 11 (November 2017) - Rubio-Bueno, P.; Landete, P.; Ardanza, B.; Vázquez, L.; Soriano, J.B.; Wix, R.; Capote, A.; Zamora, E.; Ancochea, J.; Naval-Gías, L.
Abstract: Maxillomandibular advancement (MMA) can be effective for managing obstructive sleep apnoea (OSA); however, limited information is available on the predictor surgical variables. This study investigated whether normalization of the mandibular occlusal plane (MOP) was a determinant factor in curing OSA. Patients with moderate or severe OSA who underwent MMA were evaluated by preoperative and postoperative three-dimensional (3D) scans and polysomnograms. The postoperative value of MOP and the magnitude of skeletal advancement were the predictor variables; change in the apnoea–hypopnoea index (AHI) was the main outcome variable. Thirty-four subjects with a mean age of 41 ± 14 years and 58, 8% female were analysed. The Epworth Sleepiness Scale (ESS) was 17.4 ± 5.4 and AHI was 38.3 ± 10.7 per hour before surgery. Postoperative AHI was 6.5 ± 4.3 per hour ( P <  0.001) with 52.94% of the patients considered as cured, and 47.06% suffering from a mild residual OSA with ESS 0.8 ± 1.4 ( P <  0.001). 3D changes revealed a volume increase of 106.3 ± 38.8%. The mandible was advanced 10.4 ± 3.9 mm and maxilla 4.9 ± 3.2 mm. MOP postoperative value was concluded to be the best predictor variable. Treatment planning should include MOP normalization and a mandibular advancement between 6 and 10 mm. The maxillary advancement would depend on the desired aesthetic changes and final occlusion.